Re/thinking chickens: the discourse around chicken farming in British newspapers and campaigners’ magazines, 1982–2016 - Lazutkaite, Elena (2020)
This thesis is an analysis of contemporary discourses around chicken farming in British newspapers and campaigners’ flagship magazines published between 1982 and 2016. In total, the study corpus comprises 1754 texts published in broadsheets The Guardian and The Daily Telegraph, tabloids the Daily Mirror and the Daily Mail (including their Sunday editions Sunday Mirror and Mail on Sunday) and magazines Agscene and Farm Animal Voice produced by the animal welfare organisation Compassion in World Farming and Outrage and The Uncounted Dead: Farming’s Unofficial Victims published by the animal rights organisation Animal Aid. The study applies the analytical framework of Critical Discourse Analysis in combination with Corpus Linguistics tools to analyse discursive framings and representations of chicken farming. The period between 1982 and 2016 marks a rapid growth of the chicken industry. Over the period of 34 years, global egg production has tripled to nearly 79 million tonnes and the number of chickens slaughtered for meat has tripled to nearly 66 billion. Despite the explosion in numbers, this thesis identifies the overall lack of attention and care for chickens as sentient beings in the newspapers analysed. Chicken farming is typically normalised through defining chickens as commodities, disregarding the link between chicken welfare, human welfare, and environmental issues, and excluding sources that could provide an alternative view. Normalisation and objectification are most prevalent in “factual” news stories that embrace a purportedly detached stance. Strikingly, the Guardian opinion pieces offer most in terms of addressing violence against chickens not only relative to the other newspapers, but also to the campaigners’ magazines. In the Guardian opinion pieces, the normative practices of consuming eggs and chicken flesh are made visible and stripped of their normative status through a critical examination of bias. In the campaigners’ corpora, on the other hand, chicken suffering is emphasised, and pragmatic approaches are prioritised. The thesis closes by integrating the study findings and the politics of what we eat to call for changes in discourse and practice.